The Linguistic Intelligence of Students in Applied Classical Arabic Text - Fina Aunul Kafi; Miftahul Huda (INAIFAS PRESS, 2023)
Linguistic intelligence plays an important role in helping students cope with everyday problems. This research focuses on the linguistic intelligence of students at Al-Yasiny Islamic Boarding School Jember in the study of classical Arabic texts. The research method used was auto-ethnography with observation checklists, written interviews, and questionnaires, which were tested through triangulation. The results show the development of linguistic intelligence through the application of classical Arabic texts. Language proficiency through discussion reached the highest percentage (87.2%), while reading and writing foreign languages had the lowest percentage (73.6%). This research can be used to design learning programs that support the development of students' linguistic intelligence, both in classical Arabic and foreign languages, in facing future challenges.